2017
DOI: 10.1002/andp.201700029
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Reaction Kinetics to Optimize Graphene Growth on Cu by Chemical Vapor Deposition

Abstract: Understanding and controlling the growth kinetics of graphene is a prerequisite to synthesize this highly wanted material by chemical vapor deposition on Cu, e.g. for the construction of ultra-stable electron transparent membranes. It is reviewed that Cu foils contain a considerable amount of carbon in the bulk which significantly exceeds the expected amount of thermally equilibrated dissolved carbon in Cu and that this carbon must be removed before any high quality graphene may be grown. Starting with such co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
39
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(46 citation statements)
references
References 76 publications
6
39
1
Order By: Relevance
“…In addition, the various advantages of the CVD approach include those posed by the confinement concept as well. [ 11,13,14 ] Generally, a space‐restricted configuration poses two major advantages. First, the key objective of the space‐limited chamber is to reduce the carbon (C) flux and contain the growth substrate nearby for a longer period to increase the growth probability.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the various advantages of the CVD approach include those posed by the confinement concept as well. [ 11,13,14 ] Generally, a space‐restricted configuration poses two major advantages. First, the key objective of the space‐limited chamber is to reduce the carbon (C) flux and contain the growth substrate nearby for a longer period to increase the growth probability.…”
Section: Introductionmentioning
confidence: 99%
“…In this technique, the carbon precursors are decomposed on the Cu surfaces because of its low carbon solubility and the self-limiting factor. 610 The resulting graphene on the metal substrate can be easily transferred to any desirable substrates by a simple transferring process without affecting much of the properties of graphene. Recently, gaseous hydrocarbons and liquid carbon sources have been replaced by forthcoming solid carbon sources such as camphor (C 10 H 16 O), polystyrene, and so forth by a very facile and low cost approach to achieve a large-area MLG on Cu foil with an optimum optoelectronic properties.…”
Section: Introductionmentioning
confidence: 99%
“…15,16,1922 There are various reports on the variation of annealing and gaseous flow rates to control the nucleation and growth kinetics of graphene crystals on substrate surfaces. 10,2326 In addition, various temperature conditions give an indication on the control formation of monolayer, bilayer, hexagonal structure, layer-stacking, and dendrite growth of graphene. 27,28 In this regard, the key point for the present investigation is to achieve MLG on Cu foil with a large domain size that can deliver good optical and electrical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, methane dissociation on copper is a much investigated method for creating high quality graphene. [3][4][5][6][7][8][9] However, due to the complexity of the interaction between metals and molecules and of describing both metals and molecules accurately, this reaction remains difficult for theoretical studies. [10][11][12][13][14] Recently, it has been shown that chemically accurate results can be obtained for moleculesurface reactions by using a so-called Specific Reaction Parameter (SRP) approach.…”
Section: Introductionmentioning
confidence: 99%